Prospective assessment of midsecretory endometrial leukemia inhibitor factor expression versus ανβ3 testing in women with unexplained infertility - Franasiak, Jason M. (2014)
OBJECTIVE: To evaluate endometrial leukemia inhibitor factor (LIF) expression as a marker of endometrial receptivity in women with unexplained infertility (UI). DESIGN: Prospective case-control study. SETTING: University-associated infertility clinics. PATIENT(S): Women with UI for more than 1 year and healthy control women. INTERVENTION(S): Endometrial biopsy. MAIN OUTCOME MEASURE(S): Time to pregnancy was compared between patients with UI who were evaluated for endometrial LIF protein as well as ανβ3 integrin expression. Endometrium was evaluated using immunohistochemistry (IHC) and messenger RNA by real time reverse transcriptase–polymerase chain reaction (PCR) (quantitative real-time reverse transcriptase–PCR) in samples from women with UI as well as healthy control women. RESULT(S): Leukemia inhibitor factor was expressed in epithelial cells in a cyclic fashion in controls, and overall expression in the secretory phase was similar between controls and women with UI, whereas ανβ3 integrin expression was reduced. However, using quantitative real-time PCR, LIF messenger RNA abundance was 4.4-fold lower in women with low levels of ανβ3 integrin expression compared with samples with normal integrins. By immunohistochemistry, ανβ3 integrin expression was always lacking when the histology was out of phase, whereas LIF expression was only negative in a subset of those samples. Reduced endometrial LIF expression was strongly associated with poor reproductive outcomes. CONCLUSION(S): Endometrial LIF expression peaks in the midsecretory phase and is reduced in some women with UI. The use of LIF in combination with ανβ3 integrin as biomarkers appears to be superior to integrin testing alone when evaluating endometrial receptivity, primarily because of its earlier pattern of expression during the secretory phase.